2019
DOI: 10.1002/cpt.1321
|View full text |Cite
|
Sign up to set email alerts
|

Oral Chaperone Therapy Migalastat for Treating Fabry Disease: Enzymatic Response and Serum Biomarker Changes After 1 Year

Abstract: Long‐term effects of migalastat therapy in clinical practice are currently unknown. We evaluated migalastat efficacy and biomarker changes in a prospective, single‐center study on 14 patients with Fabry disease (55 ± 14 years; 11 men). After 1 year of open‐label migalastat therapy, patients showed significant changes in alpha‐galactosidase‐A activity (0.06–0.2 nmol/minute/mg protein; P = 0.001), left ventricular myocardial mass index (137–130 g/m 2 ; P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
1
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 49 publications
(85 reference statements)
0
53
1
4
Order By: Relevance
“…However, the actual proportion of patients who can be considered for migalastat therapy is important: in contrast to a mutation database, a community of Fabry patients consists of families rather than of single mutations, and the cohort composition depends on the diagnostic approaches within a country, such as national screening programs and programs increasing physicians' awareness of the disease. In a study of the Fabry center in Würzburg (Germany), Muntze et al mentioned that 37% of their FD patients had amenable mutations, which is less than in the present Swiss Fabry cohort.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…However, the actual proportion of patients who can be considered for migalastat therapy is important: in contrast to a mutation database, a community of Fabry patients consists of families rather than of single mutations, and the cohort composition depends on the diagnostic approaches within a country, such as national screening programs and programs increasing physicians' awareness of the disease. In a study of the Fabry center in Würzburg (Germany), Muntze et al mentioned that 37% of their FD patients had amenable mutations, which is less than in the present Swiss Fabry cohort.…”
Section: Discussioncontrasting
confidence: 56%
“…In patients on ERT, it is not surprising that the change in endogenous enzyme activity does not correlate with change in lyso‐Gb3, as they were treated with exogenous enzyme. An increasing level of lyso‐Gb3 after switch to migalastat has already been observed in a recent article by Muntze et al These findings suggest that migalastat cannot stabilize important biomarkers in all patients; the clinical impact of this result needs to be further studied.…”
Section: Discussionmentioning
confidence: 71%
“…To the Editor: We thank Dr Körver and colleagues for their interest in our work. 1 We absolutely agree that validity of current amenability criteria arguably might still be subject to discussion. From the clinical viewpoint, the cutoff values of 1.2fold relative and 3% absolute increase in alpha galactosidase activity chosen in the recent multicenter trials might be questionable particularly in patients with polymorphism-like genotypes, such as the benign variant D313Y, presenting with near-normal wild-type enzyme activity but currently still categorized as amenable.…”
Section: Jonas Müntze 12 and Peter Nordbeck 12mentioning
confidence: 81%
“…A recent study showed a significant increase of leukocyte α‐Gal A activity, but not a complete normalization, in 14 FD patients (three females) after 1 year of migalastat, increasing from 0.06 (IQR 0.04–0.12) to 0.2 nmol min −1 mg −1 protein (IQR 0.06–0.26; reference values reported in the publication: 0.4–1.0 nmol min −1 mg −1 protein) (Müntze et al, ). In this study, the subgroup of p.N215S carriers ( n = 8), had an increase of α‐Gal A activity from 0.06 (0.05–0.07) to 0.2 nmol min −1 mg −1 protein (0.1–0.25) (Müntze et al, ). Although blood leukocytes are not the main therapeutic target in FD, intracellular leukocyte α‐Gal A activity reflects the amount of enzyme that could reach the lysosome via intracellular trafficking.…”
Section: Discussionmentioning
confidence: 97%